2020
DOI: 10.33395/sinkron.v5i1.10612
|View full text |Cite
|
Sign up to set email alerts
|

Facial Recognition Implementation using K–NN and PCA Feature Extraction in Attendance System

Abstract: Attendance is the fact that someone is present at an event or goes regularly to an institution, or attendance at an event is the number of people present at that time. The Saifiatul Amaliyah school itself is one of the many schools in Indonesia where the attendance of students or attendance is still done manually. This can cause problems, namely allowing fraud when filling in attendance and errors in data recapitulation. Therefore, in this study a computerized face attendance was created, which was formed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…Gambar 1. Arsitektur Penelitain (Tanjung & Wijaya, 2020) Pada gambar 1 mengilustrasikan proses pengenalan sampel wajah absen menggunakan metode klasifikasi K-NN dengan variasi rumus jarak serta PCA sebagai ekstraksi fiturnya, cara kerja penelitian ini dengan memberikan input wajah ke dalam sistem akan otomatis diekstraksi dengan PCA dan diklasifikasikan dengan algoritma K-NN dengan variasi rumus jarak berdasarkan bobot fitur wajah yang telah disediakan.…”
Section: B Arsitektur Penelitianunclassified
“…Gambar 1. Arsitektur Penelitain (Tanjung & Wijaya, 2020) Pada gambar 1 mengilustrasikan proses pengenalan sampel wajah absen menggunakan metode klasifikasi K-NN dengan variasi rumus jarak serta PCA sebagai ekstraksi fiturnya, cara kerja penelitian ini dengan memberikan input wajah ke dalam sistem akan otomatis diekstraksi dengan PCA dan diklasifikasikan dengan algoritma K-NN dengan variasi rumus jarak berdasarkan bobot fitur wajah yang telah disediakan.…”
Section: B Arsitektur Penelitianunclassified
“…Perguruan Tinggi memiliki otonomi di bidang akademik yang salah satunya melaksanakan penelitian [1].Di sinilah letak pentingnya peran seorang dosen dalam sebuah institusi perguruan tinggi Demikian pentingnya peran dosen di dalam aktivitas perguruan tinggi sehingga perlu dijaga kualitas kinerjanya khususnya Penelitian. Penelitian Dosen Universitas Graha Nusantara Padangsidimpuan di Data Simlitabmas Masih masuk Kategori Binaan [2]. Sedangkan Visi Universitas Graha Nusantara (UGN) Padangsidimpuan Menjadi Perguruan Tinggi yang Unggul , Mandiri dan Mampu Bersaing Secara Nasional pada Tahun 2030.…”
Section: Pendahuluanunclassified
“…The KNN algorithm has been popularly used as an approach used in image classification. KNN has results that show it can classify images efficiently and also successfully identify with accuracy and have high resilience (Vaishnnave, Devi, Srinivasan, & Jothi, 2019) (Tanjung & Wijaya, 2020) (Alkababji & Jbaar, 2021). Several previous studies have shown that KNN can produce high accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%